Bread Winner : an intimate history of the Victorian economy - Griffin, Emma (Yale University Press, 2020)
The overlooked story of how ordinary women and their husbands managed financially in the Victorian era - and why so many struggled despite increasing national prosperity. Nineteenth century Britain saw remarkable economic growth and a rise in real wages. But not everyone shared in the nation's wealth. Unable to earn a sufficient income themselves, working-class women were reliant on the 'breadwinner wage' of their husbands. When income failed, or was denied or squandered by errant men, families could be plunged into desperate poverty from which there was no escape. Emma Griffin unlocks the homes of Victorian England to examine the lives - and finances - of the people who lived there. Drawing on over 600 working-class autobiographies, including more than 200 written by women, Bread Winner changes our understanding of daily life in Victorian Britain.